THE EFFECT OF PROJECT-BASED LEARNING TOWARD STUDENTS’ NARRATIVE SPEAKING SKILL - Septiana, Anisa Amalia; Mubarok, Husni (Esteem Journal of English Education Study Programme, 2025)
To address persistent challenges in students’ speaking proficiency, the researcher adopted the Project-Based Learning (PJBL) approach as a pedagogically sound alternative. This study aimed to evaluate the effectiveness of PJBL in enhancing learners' narrative speaking abilities. Carried out at MA Mathalibul Huda Mlonggo, the investigation involved Grade 10 students from the MIPA 1 and MIPA 2 streams. Employing a quantitative research paradigm with a Quasi-Experimental Design, data were subjected to statistical analysis using an independent samples t-test via SPSS version 25. The outcomes revealed that the PJBL strategy significantly enhanced students’ narrative speaking performance, as evidenced by a post-test mean score of 77.56 in the experimental cohort, notably surpassing the control group's mean of 66.22. The significance value of 0.000—well below the conventional alpha threshold of 0.05—confirmed a statistically meaningful disparity between the two groups. In light of these findings, English language educators are strongly encouraged to integrate PJBL into their instructional repertoire to foster more dynamic, creative, and learner-centered environments for narrative learning. The approach has proven effective in cultivating a communicative and participatory classroom atmosphere. This study concentrated on the implementation processes, classroom dynamics, and educational outcomes linked to the application of PJBL